2015
DOI: 10.3389/fnhum.2015.00577
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of coordinative training on normal weight and overweight/obese children’s attentional performance

Abstract: This study investigated the efficacy of a physical activity (PA) program to improve the attention span in normal weight vs. overweight/obese children. The study was designed as a cluster-randomized controlled intervention. One hundred fifty-seven normal weight and overweight/obese primary school children were randomly divided in three cohorts: Traditional PA, Coordinative PA and a Control group (not attending any PA). Before and after 5 months of intervention, children were administered the d2-R test of attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 44 publications
2
32
2
2
Order By: Relevance
“…Results from chronic intervention studies focusing on moderate-to-vigorous physical activity have also pinpointed these positive effects (e.g., Hillman et al, 2014). Moreover, single bouts of coordinatively demanding physical activity have been found to improve attention in adolescents (Budde et al, 2008), and chronic interventions employing coordinatively demanding physical activity have successfully improved children's attention (Chang et al, 2013; Gallotta et al, 2015). Attention is a key mediator of hippocampal-related declarative memory formation (Aly and Turk-Browne, 2016), probably related to schema-dependent academic learning and performance (van Kesteren et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Results from chronic intervention studies focusing on moderate-to-vigorous physical activity have also pinpointed these positive effects (e.g., Hillman et al, 2014). Moreover, single bouts of coordinatively demanding physical activity have been found to improve attention in adolescents (Budde et al, 2008), and chronic interventions employing coordinatively demanding physical activity have successfully improved children's attention (Chang et al, 2013; Gallotta et al, 2015). Attention is a key mediator of hippocampal-related declarative memory formation (Aly and Turk-Browne, 2016), probably related to schema-dependent academic learning and performance (van Kesteren et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Each module focuses on specific coordination abilities found in sports games, rhythmic activities, gymnastics and/or fitness activities. These activities were previously published by our lab ( Gallotta, 2014 ; Gallotta et al, 2014 ; Gallotta et al, 2015 ). The capacities requested were: static and dynamic balance, combination, kinesthetic differentiation, spatial orientation, rhythm and reaction.…”
Section: Methodsmentioning
confidence: 99%
“…It was primarily focused on endurance, strength, flexibility exercises and circuit training for cardiovascular health ( Decree of the President of the Republic of Italy of 16 November 2012, 2013 ). The specialist PE teacher proposed exercises without high coordinative demands with the main goal of developing children’s physical characteristics ( Gallotta et al, 2015 ), (see Appendix for full protocol description).…”
Section: Methodsmentioning
confidence: 99%
“…cognitive and motor demands) characteristics, most of the studies have focused on the quantitative characteristics of the physical activity (Drollette et al, 2014;Fisher et al, 2011;Hillman et al, 2009) which have been shown to positively affect the central nervous system through physiological responses to the physical activity (Hillman et al, 2008). Besides studies of quantitative characteristics, recent studies have also highlighted the positive effect of the qualitative characteristics of the physical activity, suggesting that the type of activity is also important (Budde et al, 2008;Gallotta et al, 2015;Jäger et al, 2014;Pesce et al, 2009). The assumption behind this cognitive stimulation hypothesis is that coordinatively demanding and non-automated movement and sports actions engage the same brain regions that are used to control higher order cognitive processes (Tomporowski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%